PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI EDAMAME (Glycine max (L) Merill) DENGAN PEMBERIAN PUPUK KANDANG AYAM DAN Trichoderma sp. - Suhada, Al Hafiz; Yetti, Husna; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Increased productivity of edamame soybean crops with the addition of chicken manure and the use of Trichoderma sp as a decomposer of organic matter. This study aims to determine the interaction and the influence of single factor of chicken manure and Trichoderma sp. and to find out the best dose of edamame soybean growth and yield. This experiment was conducted experimentally in a 3x3 factorial formulated according to a complety randomized design (RAL) consisting of two factors: chicken manure (5,10 and 15 t.ha-1) and Trichoderma sp. (without application, 10 g, and 15 g). The parameters observed were percentage of effective root nodule, plant height, flowering age, percentage full pod, weight of pod per plant, number of seeds per pod, production per plot. then tested further by Duncan's multiple-range test at a 5% level. The results showed that the application of single factor of chicken manure and Trichoderma sp. effect on plant height, flowering age, number of pods, plant pod weight, and plot production but no effect on the percentage of effective root nodule and number of seeds per pod and 10 g of Trichoderma sp. and 10 t.ha-1 chicken manure is a treatment that may be the best dose to increase the growth and production of edamame soybean crop.Keywords: edamame soybean, chicken manure, Trichoderma sp.